Teologi Biblika Kontekstual di Seputar Persoalan Perempuan, Keturunan, dan Kemandulan - Yohanes Krismantyo Susanta (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2020)
The issues raised in this article are women and infertility in the context of Christian theology. Interpretation of biblical texts and Christian traditions has led to injustice and discrimination, especially for women. Therefore, constructive and contextual theology is needed to realize liberating understandings for women and men. The goal to be achieved is to offer contextual biblical theology so that the meeting between culture and biblical texts produces a spirit of equality, a spirit that liberates and upholds human values. Using the synthesis model, this article shows that a reinterpretation of the texts of the Scriptures is necessary. Reinterpretation includes the nature and purpose of marriage, the role and position of women, and the theological meaning behind the story of infertility in the Scriptures. The purpose of marriage must be understood in the maturity of faith that each husband and wife are called to enjoy exclusive togetherness in the context of a covenant with God as the initiator. The Bible shows that from the very beginning, God created humans, men, and women in His image. This indicates that men and women have an equal position even though they have differences. Meanwhile, barrenness becomes rhetoric that lifts stories from women in ancient times to emphasize that God is the owner of the womb, and He has the power to control who, when, and how pregnancy occurs.